Morphology Analysis On Derivational Affixes Process In 9 Summers 10 Autumns, From The City Of Apples To The Big Apple Novel By Iwan Setyawan - Nugroho, Febbi Kusuma; , Dr. Dwi Haryanti, M.Hum; , Siti Fatimah, S. Pd, M. Hum (2014)
This study studies the derivational affixes in 9 Summers 10 Autumns, from the City of Apples to the Big Apple novel by Iwan Setyawan. The objectives of this study are to classify the types of derivational affixes in English word that are found in "9 Summers 10 Autumns, from the City of Apples to the Big Apple" novel by Iwan Setyawan and to describe the form and meaning of derivational affixes in "9 Summers 10 Autumns, from the City of Apples to the Big Apple" novel by Iwan Setyawan. This research is a descriptive qualitative research. The ata are in the form of English words which contain derivational affixes from English novel in"9 Summers 10 Autumns, from the City of Apples to the Big Apple" by Iwan Setyawan. The data are analyzed by reads the English novel in"9 Summers 10 Autumns, from the City of Apples to the Big Apple" by Iwan Setyawan, gives an underline to the English words which contain English derivational affixes, and identifies the derivational affixes process that occurs on English words. The results of the study show that firstly, from the whole data 287 there are 15 data or 5,27% belong to the derivational prefix, that consist the change of noun into noun (3 data or 1,05%), verb into verb (7 data or 2,44%), adjective into adjective (5 data or 1,74%), 65 data or 22,65% belong to the changes of verb into noun (suffix), 9 data or 3,14% belong to the changes of verb into adjective (suffix), 13 data or 4,53% belong to the changes of noun into noun (suffix), 64 data or 22,3% belong to the changes of noun into adjective (suffix), 1 data or 0,35% belongs to the changes of noun into verb (suffix), 24 data or 8,4% belong to the changes of adjective into noun (suffix), 2 data or 0,7% belong to the changes of adjective into verb (suffix), 1 data or 0,35% belongs to the changes of adjective into adjective (suffix), 76 data or 26,5% belong to the changes of adjective into adverb (suffix), 3 data or 1,05% belong to the changes of adverb into adverb (suffix), 14 data or 4,88% belong to the derivational prefix + derivational suffix, that consist the change of noun into adjective (5 data or 1,74%), verb into adjective (5 data or 1,74%), verb into noun (1 datum or 0,35%), adjective into adverb (3 data or 1,05%). Secondly, the most data collected are the affixes from adjective into adverb (-ly), which is 26,5%. While the second is affixes from verb into noun (-ation, -ant, -ion, -er, -or, -ing, -ment, -ence, -cy, -al, -ee, dis + ment), which is 22,65%. The third is affixes from noun into adjective (- al, -ish, -less, -ful, -ian, -able, -en, -ary, -ic, -ious/-ous, -y, -ar, -ny, un + able, un + ful, in + able, un + ly), which is 22,3%. The fourth is affixes from adjective into noun (-ce, -cy, -er, -ism, -ist, -ity, -ness), which is 8,4%. The fifth is affixes fromnoun into noun (-ache, -ence, -ery, -hood, -ion, -ist, -ity, -ship, dis-, mis-), which is 4,53%. The sixth is affixes from verb to adjective (-able, -ent, -ous, -ive, un + able, un + ably), which is 3,14%. The seventh is affixes from verb into verb (dis-, en-, ex-, im-, re-, un-), which is 2,44%. The eighth is affixes from adjective into adjective (-ish, im-, in-, -un), which is 2,09%. The ninth is affixes from adverb into adverb (-theless), which is 1,05%. The tenth is affixes from adjective into verb (-ify, -ize), which is 0,7%, and the last is affixes from noun into verb (-en), which is 0,35%. Thirdly, there are some lexical categories in derivational process of affixes. The researcher finds four lexicl categories in the derivational process of affixes. The lexical categories from verb into noun are 65 words, the lexical categories verb into adjective are 12 words, the lexical categories from noun into noun are 16 words, the lexical categories from noun into adjective are 67 categories, the lexical categories from noun into verb is 1 word, the lexical categories from adjective into noun are 24 words, the lexical categories from adjective into verb are 2 words, the lexical categories from adjective into adjective are 6 word, the lexical categories froma djective into adverb are 79 words, the lexical categories from adverb into adverb are 3 words, the lexical categories from verb into verb are 7 words.